Institutional Strengthening of the Maju Mandiri Farmers Group in Bonto Tallasa Village, Ulu Ere District, Bantaeng Regency: Analysis of Farmer Participation and Empowerment - Sahlan Sahlan; Maryam Maryam; Jumiati Jumiati (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
This study aims to analyze the institutional strengthening of farmer groups in Bonto Tallasa Village, Ulu Ere District, Bantaeng Regency in responding to technological and marketing developments. The main focus of the study is how farmer groups can increase their capacity by increasing access to technology and efficient marketing channels. The research method used is descriptive with a quantitative approach, through observation, interviews, and documentation. The results show that institutional strengthening through information and communication channels, marketing channels, and technology implementation can improve the performance of farmer groups. By utilizing more modern information and communication technology and more structured marketing channels, farmer groups are able to increase their income and the efficiency of their farming businesses. This study provides recommendations for strengthening the institutional capacity of farmer groups by integrating technology and more efficient markets to improve the competitiveness and welfare of farmers in rural areas.